Reaktualisasi Hukum Adat Minangkabau dalam Praktik Sewa Hak Pakai Tanah: Sebuah Analisis Sosiologi Hukum Islam - Roni Marizal Putra; Silfia Hanani (Mutawasith: Jurnal Hukum Islam, 2025)
The Minangkabau customary law, as one of the oldest customary legal systems in Indonesia, has a unique land management mechanism, particularly through the concept of ulayat land which is collectively managed by clans or tribes. The practice of leasing land use rights is one form of utilizing this ulayat land. However, the understanding of the community and government officials regarding ulayat land is not uniform, leading to conflicts related to its status and management. This study aims to analyze the re-actualization and contextualization of Minangkabau customary law in the practice of leasing land use rights through an Islamic legal sociology approach. The research method used is qualitative with literature study and document analysis, including Minangkabau customary texts, fiqh books, legislation, and scholarly journals. The research results show that the practice of leasing land use rights in Minangkabau is still influenced by local traditions, although modernization and globalization have changed land ownership patterns from communal to individual.